Technology of Intensive Planting of Sunflower and Soybean for Grain in Sandy Soils - Usmonov Nodirjon Botiraliyevich (Web of Journals Publishing, 2023)
The article describes the possibilities of growing grain crops by cultivating sunflower and soybean crops in the conditions of sandy soils of the desert region.
Keywords: Sandy soil, agrotechnology, fertilization rate, mineralized water, sunflower, soybean crop.